The evolutionary history of Neanderthal and Denisovan Y chromosomes - (:unkn) unknown (My University, 2020)
Our knowledge of ancient human population structure in sub-Saharan Africa, particularly prior to the advent of food production, remains limited. Here we report genome-wide DNA data from four children—two of whom were buried approximately 8,000 years ago and two 3,000 years ago—from Shum Laka (Cameroon), one of the earliest known archaeological sites within the probable homeland of the Bantu language group1,2,3,4,5,6,7,8,9,10,11. One individual carried the deeply divergent Y chromosome haplogroup A00, which today is found almost exclusively in the same region12,13. However, the genome-wide ancestry profiles of all four individuals are most similar to those of present-day hunter-gatherers from western Central Africa, which implies that populations in western Cameroon today—as well as speakers of Bantu languages from across the continent—are not descended substantially from the population represented by these four people. We infer an Africa-wide phylogeny that features widespread admixture and three prominent radiations, including one that gave rise to at least four major lineages deep in the history of modern humans.
Keywords: African Research